Gut Microbiota Regulates the Homeostasis of Dendritic Epidermal T Cells - Jinwoo Chung; Joo-Chan Lee; Hanna Oh; Yesung Kim; Suin Lim; Chanu Lee; Yoon-Gyu Shim; Eun-Chong Bang; Jea-Hyun Baek (Life)
Dendritic epidermal T cells (DETCs) are a γδ T cell subset residing in the skin epidermis. Although they have been known for decades, the fate of DETCs has largely remained enigmatic. Recent studies have highlighted the relationship between the gut microbiome and γδ T cells in various epithelial and non-epithelial tissues, such as the small intestine, lung, liver, gingiva, and testis. While the skin microbiota has been shown to impact skin γδ T cells, a direct relationship between the gut microbiota and DETCs remains unexplored. In this study, we investigated whether DETCs are regulated by the gut microbiota in the steady-state skin epidermis. We examined the occurrence of DETCs in Balb/c mice, which have a skin epidermis barely populated with DETCs, compared to C57BL/6 mice, under different housing conditions. Our findings reveal that local skin inflammation markedly increases DETC numbers in the ear epidermis of Balb/c mice and that DETCs are activated by environmental factors. Furthermore, an investigation of the gut microbiota under different housing conditions revealed distinct microbial compositions and functional profiles. Taken together, these results suggest a strong connection between DETCs and gut microbiota.